Gene metabolite relationships revealed metabolic adaptations of rice salt tolerance - Mojdeh Akbarzadeh Lelekami; Mohammad Hadi Pahlevani; Khalil Zaynali Nezhad; Keyvan Mahdavi Mashaki (Scientific Reports)
Abstract Environmental stresses, particularly salinity, pose significant challenges to global crop production, notably impacting the growth and yield of rice. Integrating gene expression and metabolomics data offers valuable insights into the molecular mechanisms driving salt tolerance in plants. This study examined the effects of high salinity on the roots and shoots of rice genotypes with contrasting tolerances: CSR28 (tolerant) and IR28 (sensitive) at the seedling stage. Our phenotypic and physiological assessments indicated significant differences in response to prolonged salinity exposure between the two genotypes. Notably, osmoprotectants, including amino acids and sugars, exhibited increased accumulation, whereas most organic acids showed a decline. Linear regression analyses established significant correlations between the levels of proline, myoinositol, catalase (CAT), and superoxide dismutase (SOD) and their respective encoding genes: OsP5CS2, OsIMP, OsNCA1a, and OsSOD-Fe. Furthermore, a relationship was identified between H2O2 content and the expression of glycolate oxidase (GLO), highlighting its role in initiating defense mechanisms under salinity stress. Our findings indicated specific metabolites and genes associated with distinct organs, genotypes, and timepoints that can serve as biomarkers for the development of new salt-tolerant rice varieties.